INTEGRATION OF MATHEMATICAL MODELING AND ELECTROMAGNETIC TESTING METHODS FOR ASSESSING THE TECHNICAL CONDITION OF ELECTRIC MOTORS - Djurayev Sherzod Sobirjonovich; Tukhtasinov Davronbek Hoshimjon ugli (PEDAGOGS, 2024)
Abstract. Modern in industry electricity engines main driving force from the forces one They are​ various industry in networks wide applies and their efficiency of enterprises general work to the activity directly impact shows . Therefore, electricity engines technician status regular accordingly assessment and observation important importance has . Traditional diagnostics methods sometimes limited to accuracy has there are many time and requires resources . Mathematical​ modeling and electromagnetic check methods integration to do and this problems solution in doing effective solution as manifestation is happening .